THE EFFECT OF DIFFERENT CONCENTRATION OF PAPAYA SAP FLOUR FOR QUALITY CHARACTERISTIC OF SNAKE HEAD (Channa striata) FISH SAUCE - Prastari, Cindytia; Karnila, Rahman; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was purposed to determine effect of papaya sap flour addition withdifferent concentration as catalyst to snake head (Channa striata) fish sauce fermentation. Flourof papaya sap as catalyst was containing the papain enzym components that could used to sneakhead (Channa striata) fish fermentation. The concentration of papaya sap flour was used in thisresearch was 2.5%, 5% and 7.5%. The result was dominated with protein content 59.53 (%bk).The best concentration of papaya sap flour for snake head fish sauce was 7.5% with hydrolysisvolume 81.33ml and protein amount 88.80 (%bk). Total oganoleptic value fish sauce whichmade with 2.5% concentration papaya sap flour was most favorable by consumer acceptancewith value of color 4.52, taste 5.32,textur 5.30, and odor 3.34.Keywords: Fermentation, Snake head (Channa striata), Papaya sap flour, Fish sauces